Castle swimmer. Volume two - Martin, Wendy (Comics creator) (Ten Speed Graphic, 2025)
"Two mermen reject their destinies and embark on a raucous adventure as big and unpredictable as the ocean itself--and a romance that nobody could have predicted--in the stunning second installment of the hit Webtoon series Castle Swimmer"--